THE LIS STUDY (LYUBERTSY STUDY OF MORTALITY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION). EVALUATION OF THE PHARMACOTHERAPY. PART 1. TREATMENT OF PATIENTS BEFORE MYOCARDIAL INFARCTION AND ITS INFLUENCE ON HOSPITAL MORTALITY RATE - S. Y. Marcevich; M. L. Ginzburg; N. P. Kutishenko; A. D. Deev; V. P. Smirnov; L. Y. Drozdova; E. V. Danijel's; A. V. Fokina (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To assess the patients’ pharmacotherapy preceding the acute myocardial infarction (AMI) and to assess the effects of this therapy on hospital mortality. Material and methods. 1133 patients were enrolled into the LIS AMI register . All these patients experienced AMI leading to hospital admitting in the territory of one of the districts of the Moscow Region during 3 years. The pharmacotherapy that patients received before AMI was analyzed as well as the influence of different drugs on the hospital mortality risk. Results. 172 of 1133 patients (15.2%) died in hospital. Before admission 21.4% of patients received β-blockers, 35.3% — ACE inhibitors, 15.7% — antiplatelet drugs, 1.9% — statins. Reduction in the hospital mortality rate was shown for β-blockers [relative risk (RR)=0.542, confidence interval (CI) =0.357–0.824] and ACE inhibitors (RR=0.710, CI=0.512–0.986). Conclusion. A significant part of patients with high risk of AMI does not receive drugs with proven positive effect on the life prognosis.